Effects of selenomethionine on the growth, oxidative potential, digestive enzyme activity, and immune status of juvenile sterlet (Acipenser ruthenus) - Jarmołowicz Sylwia; Prusińska Maja; Wiszniewski Grzegorz; Schulz Patrycja; Kamaszewski Maciej; Szudrowicz Hubert; Wiechetek Wiktoria; Kawalski Kacper; Duda Arkadiusz; Sikorska Justyna; Kapusta Andrzej (Fisheries & Aquatic Life)
In a 56-day experiment, the effects of selenium-enriched yeast (SeY) on the growth, enzymatic activity of the gastrointestinal tract, oxidative stress parameters, and selected immunological parameters of sterlet, Acipenser ruthenus (L.), were analyzed. The concentration of selenomethionine (SeMet) from SeY in the feed was 0 mg kg−1 (C), 0.7 mg kg−1 feed (S1), 1.4 mg kg−1 feed (S2), and 2.1 mg kg−1 feed (S3). Statistically significant differences were found in the final fish body weight between the control and groups S1 and S3. A significant increase in lipase activity was found in the initial section of the small intestine of fish from group S3. The highest activity of the antioxidant enzymes glutathione peroxidase and superoxide dismutase was recorded in the liver of fish from group S2. Analyses of non-specific humoral response parameters showed an increase in ceruloplasmin activity in group S1. The lowest active dose of SeMet derived from yeast tested in this study that stimulated humoral immunity and fish growth was 0.7 mg kg−1 feed (S1).